2018
DOI: 10.1080/10401334.2017.1412832
|View full text |Cite
|
Sign up to set email alerts
|

Positive Outcomes of Optimizing Student–Preceptor Continuity in a Traditional Block Clerkship

Abstract: Intentional scheduling of clerkship students to enhance preceptor continuity resulted in significant positive outcomes echoing the relationship-based educational benefits of longitudinal clerkships, particularly in regards to student assessment and feedback. Clerkship directors and other medical educators should consider implementing small changes within block clerkships to maximize student-preceptor continuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Our results are consistent with prior studies that have demonstrated the positive influence of preceptor continuity in the outpatient setting 8,10,25 and hospital setting. 7,15,18,19 The studies by Bernard et al 7,15 focused on the emergency department setting, while Elnicki and Cooper 18 looked at preceptor and student reactions to increased continuity but did not investigate students' preceptor ratings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with prior studies that have demonstrated the positive influence of preceptor continuity in the outpatient setting 8,10,25 and hospital setting. 7,15,18,19 The studies by Bernard et al 7,15 focused on the emergency department setting, while Elnicki and Cooper 18 looked at preceptor and student reactions to increased continuity but did not investigate students' preceptor ratings.…”
Section: Discussionsupporting
confidence: 92%
“…Patient, peer, and preceptor continuity within the clinical learning environment has multiple benefits for medical students. [1][2][3][4][5][6] Preceptor continuity, in particular, has been associated with a number of positive outcomes, which include improved feedback to students, [7][8][9] students perceiving more accurate evaluations, 10 increased autonomy, 1,11 and increased trust from preceptors, 1,12 better overall ratings from students, 13,14 and more investment from preceptors. [15][16][17] Studies that have looked specifically at preceptor continuity in the inpatient setting have identified that increased inpatient continuity is associated with higher ratings from students 7 and faculty, 15 students perceiving higher quality feedback, 7 students performing more procedures, 11 and faculty reporting an improved ability to evaluate students.…”
Section: Introductionmentioning
confidence: 99%
“…23 Our intervention provided students with an opportunity to experience the benefits of deliberate practice and continuity of feedback which has been shown to be valuable even in comparatively short placements of between 3 and 12 weeks. 24,25 Furthermore, some student comments suggest that their theoretical knowledge base led to a propensity to think in terms of "typical" presentations and to consider only a limited number of possibilities, often within a single organ system. The fact that they were based on specialized wards made broad thinking more problematic as they started to assume that certain symptoms (e.g., nausea) belonged to certain specialties (e.g., gastroenterology).…”
Section: Discussionmentioning
confidence: 99%